Educational technology and the traditional lecture - Gabriel Jacobs (Association for Learning Technology, 1994)
I was recently invited to give a lecture at the opening of a new high-technology lecture theatre at Leeds Metropolitan University. It is one of the best examples of its kind I have seen. Its impressive features include hi-fi surround sound, an enormous back-projected screen giving superb picture quality from either a VCR or directly from a computer for live demonstrations, online facilities, the latest remote-control slide-projection equipment, complete lecturer's control panel, and several nice touches such as automatic dimming of the auditorium lights when Play is pressed on any of the hidden video playback machines. The overhead projectors and their screens are of the best quality and correctly positioned for the clearest possible display. There are also video-link facilities for spill-over into a secondary lecture theatre which itself is well fitted out in presentational equipment.